Strategi Media Promosi Objek Wisata Warung Apung Palembang Untuk Meningkatkan Minat Wisatawan - Chelsea Theodora; Mukhsin Patriansah; Aji Windu Viatra (UNIVERSITAS INDO GLOBAL MANDIRI, 2026)
Floating food stalls in Palembang represent a unique culinary tourism potential, blending the scenic beauty of the Musi River with the authentic flavors of traditional cuisine. This research is driven by the urgent need to address various challenges faced by these establishments, particularly regarding environmental cleanliness, inadequate infrastructure, and an unappealing visual image that has led to a decline in tourist interest and public trust. This study aims to create a visual identity and promotional media to enhance a positive image while strengthening local cultural values through a Visual Communication Design approach. The problem-solving plan involves integrating Palembang’s distinctive visual elements, such as Songket motifs, Musi River color palettes, and stilt house ornaments, into a comprehensive design system. The methodology employed is a qualitative descriptive approach, including field observations, in-depth interviews, and visual analysis to ensure authentic design solutions. The results indicate that a structured visual identity effectively repositions floating food stalls as modern culinary icons while preserving local wisdom. Furthermore, the implementation of tangible, non-digital media that is both educational and functional provides a new experience for visitors. In conclusion, this design serves not only as a marketing tool but also contributes significantly to building collective public awareness regarding the importance of maintaining cleanliness and the sustainability of river-based culinary tourism in Palembang for a better tourism future